EM Modeling of Antennas and RF Components for Wireless Communication Systems - Gustrau, Frank; Manteuffel, Dirk.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
The book focuses on the practical aspects of computational electrodynamics. A short review of electromagnetic field theory and an illustrative introduction to basic concepts of numerical methods provide the mathematical and physical background. The main part the book guides the reader step-by-step through the modelling process: from the initial "what question shall the model answer?", through the setting up of a computer model by creating geometry, boundary conditions, sources, $1! =(B, to post processing, validation, and optimization. A number of antenna and filter examples demonstrate the advantages and disadvantages of different numerical methods. So the book provides a realistic view on the capabilities and limits of state-of-the-art 3D-field simulators and on how to apply this knowledge efficiently to EM analysis and designing of RF applications in modern communication systems.s
Basics -- Electromagnetic Fields -- Radiofrequency and Antenna Theory -- Numerical Methods -- Numerical Methods -- Creating an Efficient Simulation Model -- Canonical Examples -- Applications -- Applications in Wireless Communications Systems.
Keywords: Engineering; Computational intelligence; Microwaves; Optical engineering; Engineering; Microwaves, RF and Optical Engineering; Computational Intelligence; Engineering, general; Electronic books